The Effect of Edamame milk on Triglyceride Levels in Diabetes Wistar Rats - Ajeng, Dhea; Ardiaria, Martha; Kurniawati, Dewi Marfu’ah; Ayustaningwarno, Fitriyono (Sports Medicine Curiosity Journal, 2022)
Type 2 diabetes is a hyperglycemic disease caused by cell insensitivity due to increasing blood glucose levels due to reduced insulin secretion. Hyperglycemia conditions have the risk to increase triglyceride levels in type 2 diabetes. Edamame milk contained isoflavones that had potential to reduce triglyceride level. To find out the effect of given edamame milk on triglyceride levels in type 2 diabetes wistar rats. A true experimental with pre-post randomized control group design towards 24 type 2 diabetes wistar rats in 4 groups. Groups K(+), P1 and P2 were induced Streptozotocin 45 mg/kgBW and Nicotinamide 110 mg/kgBW. P1 and P2 groups were given edamame milk at a dose of 1,8 ml/200grBW and 3,6 ml/200grBW for 28 days. Blood samples were taken through a retro-orbitalis plexus. Triglyceride levels were tested pre and post intervention using the GPO-PAP method. Data analysis had used Paired T test and One Way ANOVA test with Post hoc follow-up test. Triglyceride levels in P1 and P2 groups had significant differences (p<0,05) against the control groups. Edamame milk could reduce triglyceride levels of groups P1 and P2 at dose 1,8 ml/200grBW and 3,6 ml/200grBW. P2 was the highest group reduced in triglyceride levels up to 29,41±3,55 mg/dL. Edamame milk could reduced triglycerides levels in 28 days. Given an edamame milk at a dose 3,6 ml/200grBW more efficient to reduce triglyceride levels in type 2 diabestes rats significantly